Domain shuffling and site-saturation mutagenesis for the enhanced inhibitory potential of amaranthaceae α-amylase inhibitors - Rane, Ashwini S.; Nair, Vineetkumar S.; Joshi, Rakesh S.; Giri, Ashok P. (Protein Journal, 2023)
Amaranthaceae a-amylase inhibitors (AAIs) are knottin-type proteins with selective inhibitory potential against coleopteran a-amylases. Their small size and remarkable stability make them exciting molecules for protein engineering to achieve superior selectivity and efficacy. In this report, we have designed a set of AAI pro- and mature peptides chimeras. Based on in silico analysis, stable AAI chimeras having a stronger affinity with target amylases were selected for characterization. In vitro studies validated that chimera of the propeptide from Chenopodium quinoa a-AI and mature peptide from Beta vulgaris a-AI possess 3, 7.6, and 4.26 fold higher inhibition potential than parental counterparts. Importantly, recombinant AAI chimera retained specificity towards target coleopteran a-amylases. In addition, to improve the inhibitory potential of AAI, we performed in silico site-saturation mutagenesis. Computational analysis followed by experimental data showed that substituting Asparagine at the 6th position with Methionine had a remarkable increase in the specific inhibition potential of Amaranthus hypochondriacus a-AI. These results provide structural-functional insights into the vitality of AAI propeptide and a potential hotspot for mutagenesis to enhance the AAI activity. Our investigation will be a toolkit for AAI's optimization and functional differentiation for future biotechnological applications.
Keywords: & alpha; -Amylase; -Amylase inhibitors; Amaranthaceae; Coleoptera; Peptide; Pest control

Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase